2019
DOI: 10.1186/s12920-019-0502-y
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-miRNA-mRNA expression variation profile in the urine of calcium oxalate stone patients

Abstract: Background To explore long-non-coding RNA (lncRNA), microRNA (miRNA) and messenger RNA (mRNA) expression profiles and their biological functions in the urine samples in calcium oxalate (CaOx) patients. Methods Five CaOx kidney stone patients were recruited in CaOx stone group and six healthy people were included as control group, whose midstream morning urine was collected before the patients were given any medicine on admission. After total RNA was extracted from urine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…[36][37][38] These data suggest that proproliferation processes are dysregulated in T2DM and that miR-95 may contribute to this alteration. A recent study 41 found that lnc-RDH8-4:1 may regulate miR-6776-cadherin 4 interactions in patients with calcium oxalate stones, which can activate c-Jun NH(2)-terminal kinase (JNK) signaling pathways in osteosarcoma cells and induce the production of reactive oxygen species (ROS). [39][40][41] Notably, the production of high levels of ROS, which is associated with aging, has been demonstrated to be critical for the induction and maintenance of cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] These data suggest that proproliferation processes are dysregulated in T2DM and that miR-95 may contribute to this alteration. A recent study 41 found that lnc-RDH8-4:1 may regulate miR-6776-cadherin 4 interactions in patients with calcium oxalate stones, which can activate c-Jun NH(2)-terminal kinase (JNK) signaling pathways in osteosarcoma cells and induce the production of reactive oxygen species (ROS). [39][40][41] Notably, the production of high levels of ROS, which is associated with aging, has been demonstrated to be critical for the induction and maintenance of cellular senescence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study 41 found that lnc-RDH8-4:1 may regulate miR-6776-cadherin 4 interactions in patients with calcium oxalate stones, which can activate c-Jun NH(2)-terminal kinase (JNK) signaling pathways in osteosarcoma cells and induce the production of reactive oxygen species (ROS). [39][40][41] Notably, the production of high levels of ROS, which is associated with aging, has been demonstrated to be critical for the induction and maintenance of cellular senescence. 42 MiR-3620 has been reported to regulate the cell cycle, hypoxia, and zinc binding, as well as to play a key role in macrophage dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Replication using independent samples and a different wet-lab experimental approach supported the association of CCNL1 with DKD. Based on published gene expression data from the Affymetrix ® GeneChip ® Whole Transcript Expression Arrays, CCNL1 was one of four genes differentially expressed in patients with kidney stones compared to controls (2.6 fold change, downregulated, P = 6.58E-05) ( Liang et al, 2019 ). Based on gene expression data within NephroSeq, differential gene expression was observed for CCNL1 in kidney biopsy tissues from people with kidney disease compared to controls ( Gunther et al, 2014 ; Ju et al, 2015 ; Nakagawa et al, 2015 ); no adjustment was made for cell heterogeneity in the disease compared to control collections for these gene expression datasets.…”
Section: Discussionmentioning
confidence: 99%
“…The spinal samples from the two groups were selected for microarray analysis. We used the Affymetrix® GeneChip® Whole Transcript Expression Arrays to analyze lncRNA and mRNA expression profiles, and we applied Agilent circRNA Microarray 8x60K to analyze circRNA expression profiles in the T1–T4 spinal cord segments [ 34 ]. Microarray data were obtained and analyzed by Oebiotech Corporation (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%